KEWASPADAAN BENCANA PADA WARGA SUKU DAYAK DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Ashari, Beny Dwi; Hariyono, Widodo (Pendidikan Geografi, 2014)
Abstract : Background: Merapi Volcano is located between Central Java and Yogyakarta Special Region (DIY), considered the most active volcanoes in the world and the intensity of the eruptions tend to be short between 3-7 years. The Island of Borneo, an area for the native Dayak tribesmen, known not pick volcanoes and plate tectonics Earth line. Residents